A paradigm shift in the brain-immune relationships: infiltrating macrophages in central nervous system repair - Schwartz, Michal (Henry Stewart Talks, 2013)
The CNS immune enigma, CNS response to injury, Recruitment of macrophages is insufficient, Site, dose, timing for macrophage implantation, Local and systemic immune response, Circulating T cells are needed for recovery, Protective autoimmunity vs. autoimmune disease, Two faces of macrophages, Creation of chimeric mice with head protection, Macrophages play anti-inflammatory role, Transferred monocytes promote repair, T-cells boost monocyte recruitment, Macrophages resolve microglia response, The glial scar regulates microglia / macrophages, CSPG production and degradation, CSPG and the IL-10 expressing monocytes, Co-localization of macrophages with the glial scar, Location determines macrophage phenotype, Macrophages and neuroprotection in the retina, Macrophages support progenitor cell renewal, Monocyte recruitment is limited, Type, phenotype, location, timing, Neurogenesis: highest manifestation of plasticity, CNS specific autoreactive T cells, Spatial memory, The immunological malfunction, Immunity to self and self-maintenance, Local and systemic inflammation, Circulating cells fight local inflammation, Recruitment of monocytes in Alzheimer, From immune deficiency to brain malfunction